Quality Analysis of Natural Processed Coffee Using Different Roasting Levels - Apriliyani, Mulia Dwi Nur; Savitri, Dyah Ayu; Suud, Hasbi Mubarak; Wulanjari, Distiana (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Coffee is one of the leading plantation commodities in Indonesia. High-quality coffee has a higher price than low-quality coffee. The quality of coffee is determined by the method of selecting planting materials, handling during harvest, and processing. Coffee that is processed naturally, will be dried in the form of fruit/cherry so that coffee will decrease in quality. The quality of coffee beans can be improved if the roasting process is carried out using the right roasting temperature and time. With a variety of treatments in post-harvest processing methods and roasting levels will produce different coffee quality so that appropriate treatment is needed to determine the final result of coffee with the best quality. This study used the Complete Randomized Design (CRD) method with 2 factors, namely differences in coffee types (robusta coffee and arabica coffee) and roasting levels (light roast, medium roast, and dark roast). The research variables observed were seed weight, camba density, water content, and caffeine content. The data obtained will be analyzed using analysis of variance. If there is a significant difference between treatments, then further tests will be carried out using the Duncan Multiple Range Test (DMRT) at the 5% failure level.